Information, mobile communication, and referral effects - Barwick, Panle Jia; Liu, Yanyan; Patacchini, Eleonora; Wu, Qi (American Economic Association, 2023)
This paper uses the universe of cellphone records from a Chinese telecommunication provider for a northern Chinese city to examine the role of information exchange in urban labor markets. We provide the first direct evidence of increased communication among referral pairs around job changes. Information provided by social contacts mitigates information asymmetry and improves labor market performance. (JEL D82, J62, O18, P23, P25, R23, Z13)